2014
DOI: 10.1093/ojls/gqt035
|View full text |Cite
|
Sign up to set email alerts
|

New Rationales for Women on Boards

Abstract: and the Business Case for Ethnic Minorities' (2007) 21:4 Work, Emp. and Soc'y 773, 779 (noting that decision-making on equity issues was largely made on an intuitive basis rather than through a cost-benefit analysis). 26 Colin McLaughlin and Simon Deakin, 'Equality Law and the Limits of the 'Business Case' For Addressing Gender Inequalities'(2011) University of 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…A 2012 review also showed that only 38 FTSE 100 firms set targets for the level of board gender diversity they aimed to achieve by 2015. In addition, around 40 companies refused to set any targets and many firms declined to disclose their gender diversity policy or statistics relevant to the number of women at any level of the company (Choudhury, ). The findings of later reviews reveal that the United Kingdom's experience of voluntary board gender diversity reforms was not as successful as Australia's.…”
Section: International Board Gender Diversity Reformsmentioning
confidence: 99%
“…A 2012 review also showed that only 38 FTSE 100 firms set targets for the level of board gender diversity they aimed to achieve by 2015. In addition, around 40 companies refused to set any targets and many firms declined to disclose their gender diversity policy or statistics relevant to the number of women at any level of the company (Choudhury, ). The findings of later reviews reveal that the United Kingdom's experience of voluntary board gender diversity reforms was not as successful as Australia's.…”
Section: International Board Gender Diversity Reformsmentioning
confidence: 99%
“…They reported that the boards of these firms in Turkey were male-dominated and the inclusion of female directors was positively associated with to the financial performance of companies, as measured by the return on assets, the return on equity and the return on sales. Choudhury (2014) argued that rationales for increasing women on boards should be based on both equality and economics grounds. The first is necessary as it describes the underlying problems which could rise to the lack of women on boards as well as empowers female representation to be valued in its own right, instead of in terms of business reform.…”
Section: Firm Financial Performancementioning
confidence: 99%
“…However, the agency theory does not provide a clear prediction of the association between board diversity and financial performance. The inconclusive evidence of the agency theory-based research has been described as unconvincing or methodologically challenging (Choudhury, 2014).…”
Section: Introductionmentioning
confidence: 99%